9y-2-2(4y-2)=

Simple and best practice solution for 9y-2-2(4y-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-2-2(4y-2)= equation:


Simplifying
9y + -2 + -2(4y + -2) = 0

Reorder the terms:
9y + -2 + -2(-2 + 4y) = 0
9y + -2 + (-2 * -2 + 4y * -2) = 0
9y + -2 + (4 + -8y) = 0

Reorder the terms:
-2 + 4 + 9y + -8y = 0

Combine like terms: -2 + 4 = 2
2 + 9y + -8y = 0

Combine like terms: 9y + -8y = 1y
2 + 1y = 0

Solving
2 + 1y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 1y = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 1y = 0 + -2
1y = 0 + -2

Combine like terms: 0 + -2 = -2
1y = -2

Divide each side by '1'.
y = -2

Simplifying
y = -2

See similar equations:

| -24=(x+3) | | (2c-1)(c-5)+(c-4)(c-3)= | | 6x-2(x-8)=4(x+1)+8 | | 60=2(10)+b | | 0=1/3x-21/3x+2(3/2x-6) | | 3x-12=y+-2 | | 6n=-104 | | 5x-18*4x=36 | | 60=3(10)+b | | -24+4x-x=39 | | 6x-3(x+2)=9-9x+12x | | 4s*5=54 | | x+x+0.52+x+0.52+0.39=10.91 | | v-3=0 | | 4y+32= | | 13(4x+2)=52x+26 | | 0=-5.4x+4.2-1.6x+3.8 | | 4a^2-3a+5= | | 0.15x+0.05(50,000-x)=5,000 | | -0.5c+3=3 | | 15y-2= | | x-4=[-9]+x | | 24k=6 | | s-1=12 | | 4-6x=-6x+3 | | ln(Ax)-ln(Bx^2)=1.7 | | 6(-1+10)=0 | | -1=2r+3r | | 2.3w+-3= | | Y-12=49+12 | | 0=-2x-1/4(12x-8) | | x=75+105-29 |

Equations solver categories